2023
DOI: 10.3390/cells12050711
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin and Its Phosphorylated Thr567 form Are Key Regulators of Human Extravillous Trophoblast Motility and Invasion

Abstract: The protein ezrin has been shown to enhance cancer cell motility and invasion leading to malignant behaviours in solid tumours, but a similar regulatory function in the early physiological reproduction state is, however, much less clear. We speculated that ezrin may play a key role in promoting first-trimester extravillous trophoblast (EVT) migration/invasion. Ezrin, as well as its Thr567 phosphorylation, were found in all trophoblasts studied, whether primary cells or lines. Interestingly, the proteins were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 92 publications
(129 reference statements)
0
11
0
Order By: Relevance
“…NSC668394 speci cally inhibits the phosphorylation of ezrin T567 [19]. Here, we found that the treatment with NSC668394 only during the oocyte maturation not only signi cantly reduced the in vitro maturation rate of oocytes but also affected the in vitro fertilization and early embryo development potential.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…NSC668394 speci cally inhibits the phosphorylation of ezrin T567 [19]. Here, we found that the treatment with NSC668394 only during the oocyte maturation not only signi cantly reduced the in vitro maturation rate of oocytes but also affected the in vitro fertilization and early embryo development potential.…”
Section: Discussionmentioning
confidence: 58%
“…Ezrin has multiple phosphorylation sites, such as Ser66 [9][10][11] Thr213 [12] Thr332 [13,14] Thr567 [15][16][17] Tyr145 Tyr353 and Tyr477 [18]. Phosphorylation of Thr567 is currently considered a sign of ezrin activation and is also the most studied phosphorylation site [19].…”
mentioning
confidence: 99%
“…The protocol for isolating EVTs has been previously described [ 8 ] and adapted from [ 31 ]. After washing first trimester placental samples in Ham’s F12 (Sigma, Hertfordshire, UK), chorionic villi were physically separated and digested in 0.25% ( w / v ) trypsin solution (Sigma, Hertfordshire, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The pellet containing plasma membranes was resuspended in 250 mM sucrose/50 mM Tris pH 7.4. Samples were stored at −20 °C prior to analysis via Western blot as previously described [ 8 , 9 ]. Original, uncropped, and unadjusted images are available as Supporting Information Supplementary Figure S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation